2012
DOI: 10.1080/08989621.2012.700880
|View full text |Cite
|
Sign up to set email alerts
|

Guiding the Next Generation of NIH Investigators in Responsible Conduct of Research: The Role of the Mentor

Abstract: National Institutes of Health (NIH) K award recipients and their mentors were surveyed to investigate the role of the mentor. We found that a majority of mentors provided guidance in responsible research conduct (RCR), and that most of these relationships were deemed helpful. Mentors also responded that they played a greater importance in RCR training of their mentees than the mentees reported. Our results suggest both mentors and mentees report that mentors ideally should play a more important role in RCR tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 13 publications
0
21
0
Order By: Relevance
“…values that contribute to producing the best possible scienti c knowledge, 2. values that uphold good scienti c practice and responsibilities to colleagues, 3. values that must be realized in order to be a good researcher oneself, and 4. values that embody the responsibility of scienti c researchers towards society.…”
Section: Values In Research Practicesmentioning
confidence: 99%
See 2 more Smart Citations
“…values that contribute to producing the best possible scienti c knowledge, 2. values that uphold good scienti c practice and responsibilities to colleagues, 3. values that must be realized in order to be a good researcher oneself, and 4. values that embody the responsibility of scienti c researchers towards society.…”
Section: Values In Research Practicesmentioning
confidence: 99%
“…The rst class of values, relating to truthfulness and more generally to the proper production of scienti c knowledge, often includes values such as methodological rigour, transparency [2], and fair peer review [2][3][4]. Additionally, more abstract values like inquisitiveness [1,5,6] and integrity [7] are frequently mentioned in this respect.…”
Section: Values In Research Practicesmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, select NIH K series grants include research mentorship requirements. Four of the K grant awards require the applicant to specify both a mentor and an RCR training plan; in addition to other aspects of mentoring, the mentors are expected to provide guidance and advice to help tailor the applicant's RCR instruction . In a survey of K grant awardees and their mentors, both mentees and mentors agreed that the actual importance of the mentor's role was less than what it ideally should be; only half of the K grant recipients planned on including their mentor, and 40 percent of them reported that their mentor played no role in their RCR training…”
Section: Is Current Rcr Training Effective?mentioning
confidence: 99%
“…Elizabeth Ripley et al. assert that faculty members ought to participate in a mentor training seminar to support this role and that training should include mentoring skills, ethical theory and principles, and the development of ethical deliberation and interpersonal skills …”
Section: Proposed Improvements For Rcr Trainingmentioning
confidence: 99%